Observation of Magnetic Skyrmions in Unpatterned Symmetric Multilayers at Room Temperature and Zero Magnetic Field - Casagrande-Denardin, J (Nature Publishing Group, 2019)
Magnetic skyrmions are promising candidates for the next generation of spintronic devices due to their small size and topologically protected structure. One challenge for using these magnetic states in applications lies on controlling the nucleation process and stabilization that usually requires an external force. Here, we report on the evidence of skyrmions in unpatterned symmetric Pd/Co/Pd multilayers at room temperature without prior application of neither electric current nor magnetic field. Decreasing the ferromagnetic interlayer thickness, the tuning of the physical properties across the ferromagnetic/non-magnetic interface gives rise to a transition from worm like domains patterns to isolated skyrmions as demonstrated by magnetic force microscopy. On the direct comparison of the measured and simulated skyrmions size, the interfacial Dzyaloshinskii-Moriya interaction (iDMI) was estimated, reveling that isolated skyrmions are just stabilized at zero magnetic field taking into account non-null values of iDMI. Our findings provide new insights towards the use of stabilized skyrmions for room temperature devices in nominally symmetric multilayers. © 2019, The Author(s).